Torasemide in Hypertension and Heart Failure: Re-inventing Loop Diuretic Therapy? - Manolis, Athanasios; Kallistratos, Manolis; Doumas, Michael (Current Pharmaceutical Design, 2021)
In heart failure (HF) patients, current European Society of Cardiology (ESC) guidelines recommend the use of three loop diuretics (furosemide, torasemide, bumetanide) in order to not only reduce HF hospitalizations but also improve symptoms and exercise capacity in patients with signs and/or symptoms of congestion. In addition, for the first time in hypertensive patients, European Society of Hypertension (ESH) guidelines recommend the use of torasemide. This review aimed to summarize the mode of action of loop diuretics, to present their pharmacokinetic characteristics, and to discuss their place in the management of arterial hypertension and heart failure, with special emphasis however on torasemide.
Keywords: hypertension